2006
DOI: 10.1080/00420980500495937
|View full text |Cite
|
Sign up to set email alerts
|

Spaces of Exclusivity or Connection? Linkages between a Gated Community and its Poorer Neighbour in a Cape Town Master Plan Development

Abstract: This paper considers the impact of urban South Africa's new spatial order on its already fragile social dynamics. Analysis considers the relationships between residents of a gated community and their neighbouring (non-gated) area, addressing both the attitudes and perceptions that exist amongst residents of each area towards the 'other' neighbourhood, as well as the nature of any direct contact between residents. The case study for this paper is located in a master plan private development, constructed in 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 25 publications
2
64
0
Order By: Relevance
“…Contrary to the findings of Middleton, Ziderman and Adams(1993) who found that youth did not aspire to VET, the opportunity to study at the college is a dream come true for Allan. Living in his early years in what Lemanski (2009) describes as the then "virtually derelict" area of Westlake occupied by people "squatting in the non-serviced informal settlement" and those living in the housing for homeless people (2009: p.10), he regularly travelled past the college and decided then that "[he was] going to come to this college" one day.…”
Section: The Case Studymentioning
confidence: 99%
“…Contrary to the findings of Middleton, Ziderman and Adams(1993) who found that youth did not aspire to VET, the opportunity to study at the college is a dream come true for Allan. Living in his early years in what Lemanski (2009) describes as the then "virtually derelict" area of Westlake occupied by people "squatting in the non-serviced informal settlement" and those living in the housing for homeless people (2009: p.10), he regularly travelled past the college and decided then that "[he was] going to come to this college" one day.…”
Section: The Case Studymentioning
confidence: 99%
“…The attraction of new services and infrastructure for gated community residents can improve the local economy (Sabatini and Salcedo, 2005) and increase property values (Lemanski, 2005). Gated community developments create low-skilled jobs (Salcedo and Torres, 2004;Svampa, 2001) and increase tax revenues for local governments (Le Goix, 2005).…”
Section: Economic Effectsmentioning
confidence: 99%
“…This builds on earlier research in post-apartheid South Africa addressing the social and spatial implications of fear of crime and violence in urban areas (Dirsuweit, 2002;Lemanski, 2004), as well as the role of gated communities (Landman, 2000a(Landman, , 2000b(Landman, , 2004Ballard, 2004b;Dirsuweit and Wafer, 2005;Lemanski, 2006) and Improvement Districts (IDs) (Bénit et al, 2005;Lemanski, 2005) in privatising space and facilitating exclusion in the post-apartheid city. This research focuses on the experiences of residents in two of Cape Town's previously 'white' suburbs in which the vast majority of residents are still white, and thus although a broad range of residents were interviewed, the dominant perspective in this research is 'white'.…”
Section: Introductionmentioning
confidence: 96%